Proving of Crypto Assets in the Crime of Money Laundering - Mohammad Rachman Asa; Tashya Panji Nugraha (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
The development of crypto assets as digital instruments presents new challenges, particularly in proving money laundry. The pseudonymous, cross -border nature of crypto assets, and their use of blockchain technology, complicates the evidentiary process for law enforcement. This study aims to analyze the evidence base for crypto assets in money laundering cases. The approach used in this study is statutory regulatory approaches. The data used in this study is secondary data sourced from primary and secondary legal materials. This study utilizes a literature review. The data analysis the method in this study is guided by qualitative methods to generate descriptive analytical information. The results show that proving crypto assets in money laundering crimes can be achieved through crypto assets tracking technology, which can be achieved through digital forensics, on-chain tracking, blockchain explorers, machine unsupervised learning​ clustering methods, and deep learning. Proving crypto assets in money laundering crimes can be done by reverse proof as regulated in Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes, specifically Articles 77 and 78, and Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, namely Articles 37 and 38. Article 235 paragraph (1) of Law Number 20 of 2025 concerning the Criminal Procedure Code regarding evidence. Article 5 of the Electronic Information and Transactions Law regarding evidence . In cases of money laundering crimes through crypto assets, the burden of proof carried out by the prosecutor and by the defendant must be carried out equally. Cooperation between institutions including Indonesian Financial Transaction​ Reports and Analysis Center, Authority Service​ Finance, Commission​ Eradication Corruption, Commodity​ Futures Trading Regulatory, Police Agency​ Republic of Indonesia, and the Prosecutor's Office, plays an important role in eradicating money laundering crime through crypto assets.